The Role of von Willebrand Factor in Vascular Inflammation: From Pathogenesis to Targeted Therapy - Felice Gragnano; Simona Sperlongano; Enrica Golia; Francesco Natale; Renatomaria Bianchi; Mario Crisci; Fabio Fimiani; Ivana Pariggiano; Vincenzo Diana; Andreina Carbone; Arturo Cesaro; Claudia Concilio; et al. (Hindawi Limited, 2017)
Beyond its role in hemostasis, von Willebrand factor (VWF) is an emerging mediator of vascular inflammation. Recent studies highlight the involvement of VWF and its regulator, ADAMTS13, in mechanisms that underlie vascular inflammation and immunothrombosis, like leukocyte rolling, adhesion, and extravasation; vascular permeability; ischemia/reperfusion injury; complements activation; and NETosis. The VWF/ADAMTS13 axis is implicated in the pathogenesis of atherosclerosis, promoting plaque formation and inflammation through macrophage and neutrophil recruitment in inflamed lesions. Moreover, VWF and ADAMTS13 have been recently proposed as prognostic biomarkers in cardiovascular, metabolic, and inflammatory diseases, such as diabetes, stroke, myocardial infarction, and sepsis. All these features make VWF an attractive therapeutic target in thromboinflammation. Several lines of research have recently investigated "tailor-made" inhibitors of VWF. Results from animal models and clinical studies support the potent anti-inflammatory and antithrombotic effect of VWF antagonism, providing reassuring data on its safety profile. This review describes the role of VWF in vascular inflammation "from bench to bedside" and provides an updated overview of the drugs that can directly interfere with the VWF/ADAMTS13 axis.